Treatment outcome and prognostic factors of orthograde retreatment: A retrospective study - Ponsri S. (2023)
Aims: This study aims to evaluate the outcome and prognostic factors related to post-treatment disease in orthograde retreatment after a minimum of 1-year follow-up period. Materials and Methods: A retrospective cohort study was performed. The data of all orthograde retreatment charts between January 2006 and March 2019 from two endodontic centers in Thailand were collected. Retreatment outcomes were evaluated and prognostic factors were analyzed by multivariable binary logistic regression. Results: The average recall period was 4.3 years, ranging from 1 to 12 years. The sample in the present study consisted of 245 teeth in 220 patients, of which 161 teeth (65.70%) were classified as 'healed,' 28 teeth (11.40%) were classified as 'healing,' and 56 teeth (22.90%) as 'diseased.' The bivariate analysis showed that the statistically significant factors included the presence of pre-operative lesions, the pre-operative lesion size, access opening through the crown, chlorhexidine adjunctive irrigation, and solvent usage. Multivariable binary logistic regression identified pre-operative lesions and solvent usage as significant prognostic factors with adjusted odds ratios of 6.30 (confidence interval [CI], 2.72-14.63; P 0.01) and 2.54 (CI, 1.24-5.23; P = 0.01), respectively. The healed rate was higher when the pre-operative lesions were absent and when the solvent was used. Conclusion: The healed rate of orthograde retreatment after 1 to 12 years of follow-up was 65.70% and 77.10% for a lenient success rate. Pre-operative lesion and solvent usage were significant prognostic factors. The healed rate was higher with the absence of pre-operative lesions and usage of solvent.